Brittle Deformation During Eclogitization of Early Paleozoic Blueschist - Bukała, Michał; Barnes, Christopher J.; Jeanneret, Pauline; Hidas, Károly; Mazur, Stanisław; Almqvist, Bjarne S. G.; Kośmińska, Karolina; Klonowska, Iwona; Šurka, Juraj; Majka, Jarosław (Frontiers in Earth Science, 2020)
The Tsäkkok Lens of the Scandinavian Caledonides represents the outermost Baltican margin that was subducted in late Cambrian/Early Ordovician time during closure of the Iapetus Ocean. The lens predominantly consists of metasedimentary rocks hosting eclogite bodies that preserve brittle deformation on the μm-to-m scale. Here, we present a multidisciplinary approach that reveals fracturing related to dehydration and eclogitization of blueschists. Evidence for dehydration is provided by relic glaucophane and polyphase inclusions in garnet consisting of clinozoisite + quartz ± kyanite ± paragonite that are interpreted as lawsonite pseudomorphs. X-Ray chemical mapping of garnet shows a network of microchannels that propagate outward from polyphase inclusions. These microchannels are healed by garnet with elevated Mg relative to the surrounding garnet. Electron backscatter diffraction mapping revealed that Mg-rich microchannels are also delimited by low angle (<3°) boundaries. X-ray computed microtomography demonstrates that some garnet is transected by up to 300 μm wide microfractures that are sealed by omphacite ± quartz ± phengite. Locally, mesofractures sealed either by garnet- or omphacite-dominated veins transect through the eclogites. The interstices within the garnet veins are filled with omphacite + quartz + rutile + glaucophane ± phengite. In contrast, omphacite veins are predominantly composed of omphacite with minor apatite + quartz. Omphacite grains are elongated along [001] crystal axis and are preferably oriented orthogonal to the vein walls, indicating crystallization during fracture dilation. Conventional geothermobarometry using omphacite, phengite and garnet adjacent to fractures, provides pressure-temperature conditions of 2.47 ± 0.32 GPa and 620 ± 60°C for eclogites. The same method applied to a mesoscale garnet vein yields 2.42 ± 0.32 GPa at 635 ± 60°C. Zirconium-in-rutile thermometry applied to the same garnet vein provides a temperature of ∼620°C. Altogether, the microchannels, microfractures and mesofractures represent migration pathways for fluids that were produced during glaucophane and lawsonite breakdown. The microfractures are likely precursors of the mesoscale fractures. These dehydration reactions indicate that high pore-fluid pressure was a crucial factor for fracturing. Brittle failure of the eclogites thus represents a mechanism for fluid-escape in high-pressure conditions. These features may be directly associated with seismic events in a cold subduction regime.